THE NEED FOR A STRATEGIC FRAMEWORK FOR SUSTAINABLE WAQF DEVELOPMENT IN ADDRESSING THE CLIMATE CRISIS - Muhammad, Izlawanie; Sulaiman, Syahnaz; Mohd Anim, Nur Aqilah Hazirah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Malaysia faces challenges in balancing economic growth with environmental protection, and waqf holds strong potential for long-term, community-based climate action. However, the potential of waqf to contribute to environmental initiatives, ranging from green technologies and renewable energy to wildlife and marine conservation, sustainable agriculture, reforestation, and waste management, remains largely underexamined in the Malaysian context. Existing green waqf models from other countries, like Indonesia, are not directly applicable due to Malaysia’s unique regulatory, institutional, and socio-economic context. Moreover, there is a limited understanding of the awareness, readiness, and capacity of waqf institutions to engage in climate protection. This paper aims to highlight why Malaysia urgently needs innovative and inclusive financing mechanisms to address climate change and support its sustainability agenda. It reviews the existing literature and identifies significant research gaps that justify further exploration. In particular, the study points to the necessity of developing a strategic framework for sustainable waqf development as a means of strengthening national efforts in responding to the climate crisis.